AN INVESTIGATION OF TEACHERSâS ROLE AS FACILITATORS IN TEACHING WRITING IN THE CLASSROOM (A Case Study of Lectures in a Cirebon Private University) - Purnama, Novi Dewi (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2015)
The aim of this research is to describe in the teacherâs role as facilitator in teaching writing in the classroom. This research is qualitative approach by analysis teacherâs role as facilitator thought the data that have been collected from the studentâs and the teacherâs. the technique of collecting data that used by the writer are observation in teacherâs role as facilitator, observation sheet, interview, video recording, and the result of observation. To know the kinds of teacher role as facilitator did teaching writing in the classroom. And the writer analysis teacherâs role in teaching writing in classroom by observation sheet giving mark on it and writer the correct it, until gets the result did. Then, the writer takes the conclusion of teacherâs role as facilitator and teacher interview to appropriate the teacher role in teaching writing in the classroom . this research find come that all of teacher role. Based on the result from interview the lecturer, the teacher as facilitator was applied the teacher. Key word : Teacherâs Role As Facilitator, Teaching Writing